A THRESHOLD IN SOIL FORMATION AT EARTH'S ARID-HYPERARID TRANSITION - Ewing S.A.; Owen J.; Amundson R.; Sutter B.; McKay C.P.; Nishiizumi K.; Sharp W.; Cliff S.S.; Perry K.; Dietrich W. (My University, 2006)
The soils of the Atacama Desert in northern Chile have long been known to contain large quantities of unusual salts, yet the processes that form these soils are not yet fully understood. We examined the morphology and geochemistry of soils on post-Miocene fans and stream terraces along a south-to-north (27° to 24° S) rainfall transect that spans the arid to hyperarid transition (21 to ~2 mm rain y-1). Landform ages are ≥ 2 My based on cosmogenic radionuclide concentrations in surface boulders, and Ar isotopes in interbedded volcanic ash deposits near the driest site indicate a maximum age of 2.1 My. A chemical mass balance analysis that explicitly accounts for atmospheric additions was used to quantify net changes in mass and volume as a function of rainfall. In the arid (21 mm rain y-1) soil, total mass loss to weathering of silicate alluvium and dust (-1030 kg m-2) is offset by net addition of salts (+170 kg m-2). The most hyperarid soil has accumulated 830 kg m-2 of atmospheric salts (including 260 kg sulfate m-2 and 90 kg chloride m-2), resulting in unusually high volumetric expansion (120%) for a soil of this age. The composition of both airborne particles and atmospheric deposition in passive traps indicates that the geochemistry of the driest soil reflects accumulated atmospheric influxes coupled with limited in-soil chemical transformation and loss. Long-term rates of atmospheric solute addition were derived from the ion inventories in the driest soil, divided by the landform age, and compared to measured contemporary rates. With decreasing rainfall, the soil salt inventories increase, and the retained salts are both more soluble and present at shallower depths. All soils generally exhibit vertical variation in their chemistry, suggesting slow and stochastic downward water movement, and greater climate variability over the past 2 My than is reflected in recent (~100 y) rainfall averages. The geochemistry of these soils shows that the transition from arid to hyperarid rainfall levels marks a fundamental geochemical threshold: in wetter soils, the rate and character of chemical weathering results in net mass loss and associated volumetric collapse after 105 to 106 years, while continuous accumulation of atmospheric solutes in hyperarid soils over similar timescales results in dramatic volumetric expansion. The specific geochemistry of hyperarid soils is a function of atmospheric sources, and is expected to vary accordingly at other hyperarid sites. This work identifies key processes in hyperarid soil formation that are likely to be independent of location, and suggests that analogous processes may occur on Mars. © 2006 Elsevier Inc. All rights reserved.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен